Preserving Papuan Language to Foster Social Tolerance in Children - Sherly Gaspersz; Marissa Swanda Tupamahu; Fretty Matahelumual (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Language preservation is essential in maintaining cultural identity and fostering intercultural harmony, particularly in multicultural regions like Sorong City, Papua. Specific Background: The decline in regional language use, such as the Moi language, threatens local wisdom and social cohesion, especially among younger generations. Knowledge Gap: Limited community-based initiatives integrate trilingual education with cultural tolerance training in non-formal learning settings. Aims: This study aimed to implement and evaluate the Lestarikan Bahasa Papua (LABEPA) Movement at the Egad Kairos Learning House to strengthen children’s basic vocabulary in Moi, Indonesian, and English while promoting social tolerance. Results: Conducted through staged activities—preparation, socialization, training, testing, and monitoring—the program improved children’s vocabulary mastery from 45% (pre-test) to 78% (post-test). Interactive methods, including singing, games, and cultural storytelling, enhanced engagement and comprehension. Novelty: LABEPA uniquely combines trilingual learning with cultural and tolerance education in a playful, community-driven approach, supported by tailored teaching tools such as illustrated dictionaries and flipbooks. Implications: The findings suggest that culturally grounded, multisensory language programs can effectively enhance linguistic skills and social values, offering a scalable model for language preservation and tolerance education in other multicultural contexts Highlights: Improves children’s vocabulary in Moi, Indonesian, and English. Promotes cultural awareness and social tolerance. Uses engaging, play-based and multimedia learning methods. Keywords: Language Preservation, Social Tolerance, Trilingual Education, Cultural Identity, Community Learning